1992
DOI: 10.1017/s0022215100118511
|View full text |Cite
|
Sign up to set email alerts
|

The laryngeal mask airway in ENT surgery

Abstract: We report our experience of using the laryngeal mask airway (LMA) over a period of 18 months in 217 patients undergoing a variety of otorhinolaryngological operations. Advantages over conventional intubation for both patient and surgeon are suggested in both safety, speed and economy. An inadequate airway, necessitating replacement of the LMA, only occurred on two occasions whilst two known cases of difficult intubation easily had their airways secured by use of the LMA. Protection of the lower airways from se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A majority of studies using LMA during nasal surgeries have concluded it as an effective alternative to ETT in nasal surgeries. [ 8 10 11 12 13 ] John et al . noticed no major leak of dye past the LMA cuff or staining of the larynx even after injecting 10 mL of methylene blue into the pharynx following LMA insertion.…”
Section: Discussionmentioning
confidence: 99%
“…A majority of studies using LMA during nasal surgeries have concluded it as an effective alternative to ETT in nasal surgeries. [ 8 10 11 12 13 ] John et al . noticed no major leak of dye past the LMA cuff or staining of the larynx even after injecting 10 mL of methylene blue into the pharynx following LMA insertion.…”
Section: Discussionmentioning
confidence: 99%
“…At this “light” depth of anesthesia the LMA can be used to provide a stable airway and still permit spontaneous ventilation. For otologic surgery, the LMA can be used to secure the airway when the head is not readily accessible to the anesthetist during the procedure 11 …”
Section: Discussionmentioning
confidence: 99%
“…9 Their results show that in two out of 217 patients (1%) the LMA had to be replaced with an endotracheal tube but they did not formally evaluate the LMA for contamination. Williams, Thompsett and Bailey 8 compared the laryngeal mask with the tracheal tube in a small number of nasal surgery procedures.…”
Section: Objectif : Le Masque Laryngé (Ml) Est Utilisé En Chirurgie Nmentioning
confidence: 99%